Bringing computational thinking into classrooms: a systematic review on supporting teachers in integrating computational thinking into K-12 classrooms - Zhichun Liu; Zarina Gearty; Eleanor Richard; Chandra Hawley Orrill; Shakhnoza Kayumova; Ramprasad Balasubramanian (International Journal of STEM Education, 2024)
Abstract Although computational thinking (CT) is becoming increasingly prevalent in K-12 education, many teachers find it challenging to integrate it with their classroom learning. In this systematic review, we have reviewed empirical evidence on teachers’ computational-thinking-focused professional development (PD). The findings depict the landscape of what has been done in terms of how PDs have been designed, how CT has been conceptualized, how learning outcomes have been assessed, and how teachers have been supported in integrating CT into their teaching practices. We have further summarized the lessons learned from the PDs and discussed the gaps as the field moves forward. These findings shed light on supporting teachers as the first step to creating an effective model for CT learning and development in K-12 education.